Fe2O3-Modified Porous BiVO4 Nanoplates with Enhanced Photocatalytic Activity - Cai, Ping; Zhou, Shu-Mei; Ma, De-Kun; Liu, Shen-Nan; Chen, Wei; Huang, Shao-Ming (Nano-Micro Letters, 2015)
As BiVO4 is one of the most popular visible-light-responding photocatalysts, it has been widely used for visible-light-driven water splitting and environmental purification. However, the typical photocatalytic activity of unmodified BiVO4 for the degradation of organic pollutants is still not impressive. To address this limitation, we studied Fe2O3-modified porous BiVO4 nanoplates. Compared with unmodified BiVO4, the Fe2O3-modified porous BiVO4 nanoplates showed significantly enhanced photocatalytic activities in decomposing both dye and colorless pollutant models, such as rhodamine B (RhB) and phenol, respectively. The pseudo-first-order reaction rate constants for the degradation of RhB and phenol on Fe2O3-modified BiVO4 porous nanoplates are 27 and 31 times larger than that of pristine BiVO4, respectively. We also found that the Fe2O3 may act as an efficient non-precious metal co-catalyst, which is responsible for the excellent photocatalytic activity of Fe2O3/BiVO4.